Analisis Model Pengembangan Diri Kepala Sekolah : Studi Kasus di SD Muhammadiyah 12 Pamulang, Banten - Hery Muljono; Ahmad Kosasih (Prisani Cendekia, 2022)
The principal is responsible for running the organization. School principals are subjects who have to transform their abilities through guidance, empowerment to the entire school community to achieve the goals of the institution effectively, efficiently and productively. The reality on the ground shows that there are still many schools with low student achievement, teachers and students lack discipline, the ability of teachers to manage learning is low, and the administrative staff is slow in serving customer needs. It is assumed that the principal is less able to manage and empower all available resources in the school efficiently, effectively and productively to achieve educational goals. Researchers conduct research related to the Principal's Personal Development Model Analysis.